Interdisciplinary Strategies for Strengthening Mathematical Skills in the Second Level of Primary Education (Docentes 2.0 Journal, 2026)
Interdisciplinary strategies constitute an essential pedagogical approach for fostering mathematical competencies in elementary school students, integrating disciplines to enhance learning and application in real-world contexts. The objective of this study was to apply and assess the effectiveness of interdisciplinary strategies for strengthening mathematical competencies among second-grade elementary school students. The research was conducted within the positivist paradigm, using the hypothetico-deductive method, with a quantitative approach and a quasi-experimental single-group design with pretest and posttest measurements. The study was explanatory and cross-sectional. The non-probability convenience sample consisted of 14 students. A performance test was administered, and the data were analyzed using descriptive statistics, the Shapiro-Wilk normality test (p > 0.05), a paired t-test (t(13) = 4.58, p = 0.00051), and Cohen's d effect size (d = 1.29, 95% CI [0.51 – 2.07]). The results showed a significant increase in mean scores from 8.13 to 9.86 and a reduction in standard deviation from 1.54 to 0.36, indicating a substantial improvement in performance. In conclusion, this approach promotes the development of 21st-century skills, such as critical thinking and problem-solving, and serves as an effective pedagogical tool in elementary education.
Keywords: Interdisciplinary strategies; mathematical competencies; problem-solving